Influence of magnetic field on reduction chatter and of surface roughness in end milling of Titanium Alloy - Ti-6Al-4V - Sulaiman, Syidatul Akma; Amin, A. K. M. Nurul; Arif, Muammer Din (Trans Tech Publications, Switzerland, 2012)
One of the most challenging issues in machining process is understanding the chatter phenomenon. Chatter mechanics is still not fully understood. It is inconsistent in character, making it difficult to analyze and predict. This research work investigates the influence of permanent magnets on chatter suppression in end milling of Titanium alloy (Ti-6Al-4V) using uncoated WCCo insert. The experiments were designed based on the Response Surface Methodology (RSM) approach using DESIGN EXPERT (DOE) software. The experiments were performed under two different conditions: under normal condition and under the application of magnetic fields from two permanent magnets located in opposite direction. Ti-6Al-4V was used as the work material. The resultant average surface roughness was found to be reduced by a maximum of 50% due to magnet application. Scanning Electron Microscope (SEM) was used to analyze the chip morphology. The microphotographs showed the evidence of more stable chip formation under the influence of magnetic fields.